College Accounting Fundamentals - Edwards, James Don; Thorne, Lynn (Illinois: Richard D. Irwin, 1986)
This book has been designed for students of accounting, business administration and secretariat science.
includes index
jbi, 21/03/2018
Loans
Keywords: accounting